Digital Disaster, Cyber Security, and the Copenhagen School. - Hansen, Lene; Nissenbaum, Helen (International Studies Quarterly, 2009)
This article is devoted to an analysis of cyber security, a concept that arrived on the post-Cold War agenda in response to a mixture of technological innovations and changing geopolitical conditions. Adopting the framework of securitization theory, the article theorizes cyber security as a distinct sector with a particular constellation of threats and referent objects. It is held that “network security” and “individual security” are significant referent objects, but that their political importance arises from connections to the collective referent objects of “the state,”“society,”“the nation,” and “the economy.” These referent objects are articulated as threatened through three distinct forms of securitizations: hypersecuritization, everyday security practices, and technifications. The applicability of the theoretical framework is then shown through a case-study of what has been labeled the first war in cyber space against Estonian public and commercial institutions in 2007.